ANALISIS TATALAKSANA KEBIJAKAN DAERAH BEBAS ROKOK PADA RUMAH SAKIT UMUM DAERAH SIDIKALANG - Yuli K Harefa; Elisabeth Dame Manalu; Nurmala Sari (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2019)
The Indonesian government through Health Regulations No. 36, 2009 article 115 stipulates the Non-Smoking Area policy, one of in a health facility is a hospital. Supporting the law, the Dairi District Government issued Local Regulation, No. 01, 2017 concerning Non-smoking Area on Januari 31, 2017. The purpose of this research was to analyze the implementation of Non-Smoking Area policies in Sidikalang General Hospital. This research is descriptive qualitative research. This research was conducted in Sidikalang General Hospital. The research informants consisted of key informants, main informants, additional informants. Data were analyzed by qualitative description. The results of the research show actors from the implementation of the Non-Smoking Area policy in Sidikalang Hospital, namely directors, management, visitors and patients health workers. Regarding the content that socialization has not been evenly distributed because it was delivered orally, inadequate insfrastructure, lack of employees, there were no strict sanctions. The implementation of Non-Smoking Area is not influenced by politics, but collides with the culture of the Dairi community. Whereas based on organization, lack of commitment and lack of budget. The implementation process does not run well because there is no commitment, lack of socialization, unavailability of budget. The Non-Smoking Area explanation was not evaluated to measure policy success/ failure. Compliance is very low. The audit did not run well because there were no written documents. The budget is a problem because of the lack of funds for health promotion, the addition of the amount of security, the preparing of Closed Circuit Television (CCTV) and Television (TV) in each room, constructing the wall at RSUD’s area. It is strongly recommended to Sidikalang General Hospital to re socialize the Dairi District Regent’s regional regulation on Non-Smoking Area policy, make a statement of commitment for health workers about smoking bans, submit a budget for construction of the wall around the hospital, increase the number of security personel, addition of Closed Circuit Television (CCTV).